Design and Development of Sleep Apnea Detection Device - Khalil, Noor ALhada; Jawad, Aya Hatem; hamza, Maryam oliwie (American Journal of Biodiversity, 2025)
Patients who already suffer from sleep apnea due to the causes of this disease a lot, where the patient can be helped by monitoring their sleep conditions and the development of the disorder from the normal stages to the dangerous stages to avoid any problems that lead to stopping breathing and the occurrence of apnea and a lack of oxygen, which leads to the death of the person . We have built and designed an electronic model that diagnoses apnea continuously, especially during sleep times, and it will be placed on the patient’s chest depending on the measurement of many vital parameters such as chest movement sensor (heartbeat), oxygen saturation by pulse oximeter that is affected by breathing rate, Monitor the patient’s temperature and humidity using sensors.